Mao, Nehru and the Sino-Indian Border Dispute: A Poliheuristic Analysis. (June 2019) - Westcott, Stephen P.
The Sino-Indian border dispute has been effectively stalemated since the end of the 1962 Border War and remains a source of serious tension between the two Asian giants. Yet there were several instances throughout the 1950s and the early 1960s when the two sides could have resolved their dispute amicably. Curiously, despite several detailed historical accounts on how the Sino-Indian border dispute developed, there has been few systematic theoretical accounts exploring why this occurred. To address this gap, I utilise poliheuristic choice theory to examine the choices of the both the key decision-makers of the time, Mao Zedong and Jawaharlal Nehru. The poliheuristic choice theory illuminates why both Mao and Nehru initially chose status quo policies before embracing either compromise or escalation policies, when faced with domestic pressure at home and ideological impulses.